Optimizing Student Potential Through The Role Of Student Management - Nurlatifah, Mahanani; Kurniawan, Benny; Sudadi; Muna Fauziah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study discusses the optimization of student potential through the role of student management. The study was conducted at Ma'arif 1 Vocational High School, Kebumen. The research approach used was qualitative research. The informants of this study included the vice principal for student affairs, extracurricular teachers, and students. Research data were obtained from in-depth interviews, observations, and documentation. Triangulation of methods and sources was used in this study. Data were analyzed by collecting data, reducing data, presenting data, and verifying/drawing conclusions. The research findings indicate that student management has been attempted to optimize student potential through several stages, namely the acceptance of new students, the majority of whom are through the regular route, the orientation process for new students to introduce students to the school environment, student attendance as additional value for students during learning, grouping students according to student interests, fostering student discipline to get used to positive activities in everyday life, developing potential through mandatory and elective extracurricular activities, majoring according to student choices at the beginning of school/beginning of the semester, and the student graduation process which is marked by more than 50% of students having worked according to their expertise. This study concludes that optimizing student potential can be achieved through appropriate and sustainable student management.